Teachers’ Perceptions of Translanguaging as a Decolonial Pedagogy in South African Multilingual Classrooms - Sefotho, Malephole Philomena (Journal of Languages and Language Teaching, 2025)
Majority of people, nowadays, are bi/multilingual due to mobility and globalisation. Consequently, this has brought about decolonisation of some colonial practices that were employed during the colonial period.  One of the colonial practices was the use of ‘one language at the time’ in classroom settings which was grounded on the colonial ‘monolingual-bias’ notion. In South Africa, teachers seem to employ this practice regardless of the bi/multilingual classroom contexts. For example, when it is time for English lesson, they only allow the use of English only and no other language to avoid ‘contamination’. The purpose of this study was to examine perceptions of teachers on the use of more than one language. It further explores the use of translanguaging as a pedagogy that could be used to do away with language boundaries that were created during the colonial era.  Participants were purposively sampled language teachers at bilingual primary schools in SOWETO, Johannesburg, South Africa.  The study adopted a qualitative research design from which semi-structured interviews and observations were used. Thematic analysis was employed to analyse data.  The findings demonstrate that teachers are reluctant to allow the use of more than one language at a time in their classrooms. Their reluctance is grounded on the belief of the monolingual bias theory to avoid language ‘contamination’.  This study recommends translanguaging as a practical approach for a decolonial move where bilingual learners will be allowed to use all their linguistic repertoires for better comprehension and meaning making.